Translation and cultural adaptation of the King’s Brief Interstitial Lung Disease health status questionnaire for use in Brazil - Silveira,Karoline (2019)
ABSTRACT Objective: To translate the King’s Brief Interstitial Lung Disease (K-BILD) questionnaire to Portuguese and culturally adapt it for use in Brazil. The K-BILD quantifies the health status of patients with ILD. Methods: The process involved the following steps: authorization from the author of the original (English-language) questionnaire; translation of the questionnaire to Portuguese by three translators, working independently; merging of the translations by a committee of specialists; back-translation of the questionnaire to English; revision and readjustment of the back-translation by the committee of specialists; evaluation by the original author; revision of the back-translation; cognitive debriefing (verification of the clarity and acceptability of the Portuguese-language version in the target population-i.e., patients with ILD); and finalization of the Portuguese-language version. Results: In the cognitive debriefing step, 20 patients with ILD were interviewed. After the interviews, the clarity and acceptability index of each question was ≥ 0.8, which is considered acceptable. Conclusions: The Portuguese-language version of K-BILD appears to be easily administered to and understood by patients with ILD in Brazil. To our knowledge, this is the only instrument in Brazilian Portuguese that is designed to evaluate the impact that ILD has on the various aspects of the lives of those it affects.